Electrophilic Amination with Anthranils through Thioamide-Assisted Cobalt(III)-Catalyzed C(sp3)–H Activation - Liu, Lei; Zhang, Zhao; Wang, Yucheng; Zhang, Yan; Li, Jie (Synthesis, 2020)
Cobalt(III)-catalyzed electrophilic amination of inert C(sp3)–H bonds of weakly coordinating thioamides with readily accessible anthranil derivatives was accomplished under mild conditions, with good functional group tolerance, thus providing various amino aldehydes and amino ketones. Moreover, our protocol with the versatile [Cp*Co(MeCN)3][SbF6]2 features excellent atom-economy and oxidant-free conditions, and allows facile late-stage functionalization.
Keywords: C(sp3)–H activation; electrophilic amination; cobalt(III) catalysis; anthranils; thioamides